e-Service Quality and e-Trust Models in Increasing Generation Z e-Customer Satisfaction in e-Wallet Transactions with ShopeePay Application - Syifa Pramudita Faddila; Laras Ratu Khalida; Robby Fauji (Institute of Computer Science (IOCS), 2022)
The rapid development of the digital world, one of which is marked by changes in traditional transactions to digital transactions through digital wallets (e-Wallet). E-Wallet competition in Indonesia is quite tight, ShopeePay has decreased its position in terms of the most frequently used e-Wallet in 2020 and 2021. So it is necessary to do further research as an effort to increase e-Customer Satisfaction through e-Service Quality variables and e-Trust especially among Generation Z as a characteristic that is close to the digital world. The study was conducted on 166 students of the Management Study Program at the University of Buana Perjuangan Karawang class of 2019 – 2021 who are Generation Z and active users of ShopeePay. This study uses multiple linear regression analysis. The results of the study explain that e-Service Quality and e-Trust have a significant effect on e-Customer Satisfaction either partially or simultaneously. The higher the e-Service Quality and e-Trust provided by the company to consumers, the higher the e-Customer Satisfaction for Generation Z users of the ShopeePay application e-Wallet.